Fatty acid profile and beef quality of Nellore and Angus bulls fed whole shelled corn - Priscilla Dutra Teixeira; Jon P. Schoonmaker; José Rodolfo Reis de Carvalho; Cristhiane Viol Ribeiro de Oliveira; Aline de Castro Rodrigues; Luana Ruiz dos Santos; Marcio Machado Ladeira (Scientia Agricola, 2021)
ABSTRACT: This study aimed to evaluate the quality traits and fatty acid profile of beef from Nellore and Angus bulls fed whole shelled corn (WSC) and ground corn plus maize silage (GC) diets. Eighteen Nellore and 18 Angus young bulls [381 ± 12 kg initial body weight (BW) and an average age of 20 ± 1.9 months] were used in a completely randomized design using a 2 × 2 factorial arrangement and were slaughtered at a final BW of 451.5 kg and 545.5 kg, respectively. Twenty–four hours after slaughter, samples of longissimus thoracis muscle were collected for the analysis of lipid oxidation, color, fatty acid profile, shear force, and cooking loss. There was no effect of diet × breed interaction on meat color, lipid oxidation, shear force, and cooking loss. Angus beef had lower shear force (p < 0.05) than Nellore beef and had a greater concentration of linoleic acid and polyunsaturated fatty acids (PUFA) (p < 0.01). Beef of bulls fed WSC tended to have greater concentration of CLA C18:2c9t11 (p = 0.09), greater concentration of CLA C18:2t10c12 (p = 0.01), and PUFA (p = 0.05), and consequently, higher oxidation levels. Angus bulls produced beef with greater tenderness and PUFA concentration. The results of fatty acid show a possible change in biohydrogenation when animals are fed the WSC diet, reducing lipogenesis, as this diet increases the C18:2t10c12 content.